1984
DOI: 10.1002/mpo.2950120306
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the timing of triple intrathecal therapy on remission induction in childhood acute lymphoblastic leukemia: A pediatric oncology group study

Abstract: Five weekly doses of triple intrathecal (IT)chemotherapy (methotrexate, hydrocortisone, cytosine arabinoside) starting on day 1 of treatment were added to systemic induction therapy in a regimen (Arm 3) that was compared to three other regimens (Arms 1,2, and 4) in which central nervous system (CNS) prophylaxis was initiated after complete marrow remission (CR) was attained. The CR rate for Arm 3 was only 83% as compared to 91-92% for other Arms. The lower CR rate was the result of a significantly higher death… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Regarding the initial IT therapy schedule, a POG study demonstrated that ITT starting on day 1 of systemic treatment increased mortality mainly due to infections during induction [89]. The Taiwan Pediatric Oncology Group (TPOG) ALL-2002 trial also demonstrated that delaying initial IT therapy after the clearance of blasts in peripheral blood or performing it within ten days of the start of induction therapy did not worsen the outcomes and eliminated traumatic lumber punctures with blasts [90].…”
Section: Intrathecal Therapymentioning
confidence: 99%
“…Regarding the initial IT therapy schedule, a POG study demonstrated that ITT starting on day 1 of systemic treatment increased mortality mainly due to infections during induction [89]. The Taiwan Pediatric Oncology Group (TPOG) ALL-2002 trial also demonstrated that delaying initial IT therapy after the clearance of blasts in peripheral blood or performing it within ten days of the start of induction therapy did not worsen the outcomes and eliminated traumatic lumber punctures with blasts [90].…”
Section: Intrathecal Therapymentioning
confidence: 99%